Republic of Croatia : First Review of the Stand-By Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The Croatian authorities are likely to either meet or exceed the original growth, inflation, and international reserves objectives under the Stand-By Arrangement. Executive Directors commended the program, and stressed the need to maintain fiscal sustainability, and reduce public wages and employment from unsustainable levels. They welcomed the Croatian National Bank for pursing price stability, and emphasized the need to maintain fiscal and monetary policies, and accelerate structural reforms. Directors agreed that Croatia has successfully completed the first review under the Stand-By Arrangement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet